Strategi Komunikasi Badan Meteorologi Klimatologi dan Geofisika (BMKG) Aceh dalam Mengantisipasi Berita Hoax Gempa Aceh - Rahmawati; Rachmad Kurniawan; Mawaddah (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
This research examines how to Anticipate News of the Aceh Earthquake Hoax in Online Media. The rise of hoax news, especially regarding the earthquake that will occur on the coastal beaches of Pidie Jaya, Sigli, and Banda Aceh through social media and online media that mentions sources from BMKG. The theory of planning (theory of planning) is used as a reference by researchers as a theoretical foundation in this study to describe the planning process by the Aceh BMKG in planning communication strategies to anticipate news of the Aceh earthquake hoax through online media so as not to cause problems in the future. This theory states that the more knowledge one has, the more complex the plan will be made. This research uses descriptive qualitative methods and data collection techniques used are observation, interviews and documentation. The results of this study are the communication strategies of BMKG Aceh that have been implemented well by agencies, one of which is in anticipation of hoax news in the name of BMKG Aceh and this strategy has met the criteria of a form of communication strategy of an organization that has been summarized.